On the eigenvalues of the fredholm operator - Sheremeta, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove that if ω(t, x, K 2 (m) )⩽c(x)ω(t) for allxε[a, b] andx ε [0,b-a] wherec ∈L 1(a, b) and ω is a modulus of continuity, then λ n =O(n −m-1/2ω(1/n)) and this estimate is unimprovable.